Design of conformal antennas for V2X communications - Guo, Weijia (2015)
The final year project is a fourth year module in the School of Electrical and Electronic Engineering (EEE). This final year project studied the optimal designs of microstrip patch antenna as well as the printed dipole antenna. These two types antenna were designed to support networks such as the V2X network and DTV radar system. Through the literature review, understanding, analyzing the problem as well as the proposed solutions. Design, simulation and experiments have been carried out. On the basis of this design, the operating principals and the factors affecting performances are learnt. Few modifications have been proposed and simulated based on the standard designs which include adding reflector and sleeves, changing the dipole arms to the bow tie shape, adjusting the patch size, the feeding position as well as the conform the patch antenna to the curve shape. This report include the research on microstrip patch antenna, printed dipole antenna as well as the microstrip monopolar patch antenna, the objective of the project include theoretical calculation, design and the realistic computer based simulation using HFSS. The analysis and the suggestion will be given according to the simulation and experiment results.